Gene Regulation by Cytokinin in Arabidopsis - Brenner, Wolfram G.; Ramireddy, Eswarayya; Heyl, Alexander; Schmülling, Thomas (Frontiers in Plant Science, 2012)
The plant hormone cytokinin realizes at least part of its signaling output through the regulation of gene expression. A great part of the early transcriptional regulation is mediated by type-B response regulators, which are transcription factors of the MYB family. Other transcription factors, such as the CYTOKININ RESPONSE FACTORS of the AP2/ERF family, have also been shown to be involved in this process. Additional transcription factors mediate distinct parts of the cytokinin response through tissue- and cell-specific downstream transcriptional cascades. In Arabidopsis, only a single cytokinin response element to which type-B response regulators bind has been clearly proven so far, which has 5′-GAT(T/C)-3′ as a core sequence. This motif has served to construct a synthetic cytokinin-sensitive two-component system response element, which is useful for monitoring the cellular cytokinin status. Insight into the extent of transcriptional regulation has been gained by genome-wide gene expression analyses following cytokinin treatment and from plants having an altered cytokinin content or signaling. This review presents a meta analysis of such microarray data resulting in a core list of cytokinin-response genes. Genes encoding type-A response regulators displayed the most stable response to cytokinin, but a number of cytokinin metabolism genes (CKX4, CKX5, CYP735A2, UGT76C2) also belong to them, indicating homeostatic mechanisms operating at the transcriptional level. The cytokinin core response genes are also the target of other hormones as well as biotic and abiotic stresses, documenting crosstalk of the cytokinin system with other hormonal and environmental signaling pathways. The multiple links of cytokinin to diverse functions, ranging from control of meristem activity, hormonal crosstalk, nutrient acquisition, and various stress responses, are also corroborated by a compilation of genes that have been repeatedly found by independent gene expression profiling studies